2020
DOI: 10.1007/s00392-020-01619-8
|View full text |Cite
|
Sign up to set email alerts
|

Atrial inflammation in different atrial fibrillation subtypes and its relation with clinical risk factors

Abstract: Objective Inflammation of the atria is an important factor in the pathogenesis of atrial fibrillation (AF). Whether the extent of atrial inflammation relates with clinical risk factors of AF, however, is largely unknown. This we have studied comparing patients with paroxysmal and long-standing persistent/permanent AF. Methods Left atrial tissue was obtained from 50 AF patients (paroxysmal = 20, long-standing persistent/permanent = 30) that underwent a left atrial ablation procedure either or not in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
2
19
1
Order By: Relevance
“…Although we did not analyse atrial arrhythmia or contractility in this study, increases in immune cell infiltration and fibrosis have been described repeatedly in the atria of patients with AF 5,6 . Moreover, infiltrated lymphocytes were shown to induce altered atrial contractility, including dysrhythmia and a decrease in tension, in mice with autoimmune myocarditis 16 .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although we did not analyse atrial arrhythmia or contractility in this study, increases in immune cell infiltration and fibrosis have been described repeatedly in the atria of patients with AF 5,6 . Moreover, infiltrated lymphocytes were shown to induce altered atrial contractility, including dysrhythmia and a decrease in tension, in mice with autoimmune myocarditis 16 .…”
Section: Discussionmentioning
confidence: 76%
“…8 Although we did not analyse atrial arrhythmia or contractility in this study, increases in immune cell infiltration and fibrosis have been described repeatedly in the atria of patients with AF. 5,6 Moreover, infiltrated lymphocytes were shown to induce altered atrial contractility, including dysrhythmia and a decrease in tension, in mice with autoimmune myocarditis. 16 Lastly, we have shown recently that CVB3-induced VM led to transient changes in myocardial electrical conduction that were strongly associated with the ventricular cellular inflammatory infiltrate.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study regarding CD45 + and CD3 + cell infiltrates in the atria from patients with AF indicated that inflammatory cell infiltrates were significantly higher in patients with paroxysmal or non‐paroxysmal AF, being greater in the adipose tissue rather than in the myocardium. In addition, inflammation was more related to age and C‐reactive protein (CRP) blood levels than gender or diabetes 106 . The pro‐inflammatory cytokine, IL‐6, and CCRP are correlated with P wave variations in patients with different inflammation‐related diseases.…”
Section: Pathophysiological Mechanisms Of Af Related To Eatmentioning
confidence: 99%
“…Viral infection may be another trigger for AF development. Infections with multiple viruses, including influenza virus, hepatitis viruses, human immunodeficiency virus and human herpes viruses, have been shown to be significantly associated with AF development [3][4][5][6][7]. Moreover, the increased expression of Toll-like receptor 2 on monocytes [8] and high enrichment of viral response genes in lymphocytes [9], which have been found in AF patients, suggest an involvement of (chronic) viral infection in AF pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…AF progression is associated with structural atrial remodelling, typified by increased atrial fibrosis and fatty infiltration, which disrupts electrical signal conduction, thus facilitating atrial arrhythmia. Inflammation may be a key driver of this process and inflammatory cell infiltration is indeed commonly observed in the atria of AF patients [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%